LEGAL PROTECTION OF YEI PEOPLE'S KNOWLEDGE OF LOCAL MEDICINES AND MEDICINAL PLANTS FROM EXTINCTION - Purwanda, Sunardi; Rado, Rudini Hasyim; Susanti, Diana Sri; Zainuddin, Asriadi; Syahril, Muh. Akbar Fhad (Masalah-Masalah Hukum, 2024)
Food security investments have brought conflict between local indigenous communities and the government in South Papua. The research aims to encourage protection and recognition efforts from the state towards indigenous peoples' entities. This research uses socio-legal studies. The research found sixteen plants that function as medicine. Inventory in the form of "recording" communal intellectual property is the first step to protecting all communal intellectual property that has never been recorded before. The Yei Indigenous People or the local government should work together to register with the Ministry to obtain rights to communal intellectual property, which will impact state action in protecting and defending communal intellectual property rights.